Hi

dave13(Q) The sum of the ages of Doris and Fred is y years. If Doris is 12 years older

than Fred, how many years old will Fred be y years from now, in terms of y?

The best method is to write equations from the question stem

D + F = y -> (1)

D = F + 12

Rewriting, D - F = 12 -> (2)

Adding (1) and (2), we will get \(2D = 12 + y\) -> \(D = 6 + \frac{y}{2}\)

Substituting this value of D in equation (1)

\(F = y - D\) = \(y - (6 + \frac{y}{2})\) = \((y - \frac{y}{2}) - 6\) = \(\frac{y}{2} - 6\)

Therefore, Fred will be \(y + (\frac{y}{2} - 6)\) = \(\frac{3y}{2} - 6\) years old, y years later.

_________________

You've got what it takes, but it will take everything you've got